PPARγ disease gene network and identification of therapeutic targets for prostate cancer - Venkatachalam, G.; Kumar, Alan Prem; Sakharkar, K.; Thangavel, S.; Clement, M.; Sakharkar, M. (informa UK Ltd, 2011)
Peroxisome proliferator-activated receptor (PPAR) belongs to the nuclear hormone receptor superfamily. Recently published reports demonstrate the importance of a direct repeat 2 (DR2) as a PPARγ-responsive element in addition to the canonical direct repeat 1 (DR1) Peroxisome proliferator response elements (PPREs). However, a comprehensive and systematic approach to constructing de novo disease-specific gene networks for PPARγ is lacking, especially one that includes PPARγ target genes containing either DR1 or DR2 site within their promoter region. Here, we computationally identified 1154 PPARγ direct target genes and constructed the PPARγ disease gene network, which revealed 138 PPARγ target genes that are associated with 65 unique diseases. The network shows that PPARγ target genes are highly associated with cancer and neurological diseases. Thirty-eight PPARγ direct target genes were found to be involved in prostate cancer and two key (hub) PPARγ direct target genes, PRKCZ and PGK1, were experimentally validated to be repressed upon PPARγ activation by its natural ligand, 15d-PGJ2 in three prostate cancer cell lines. We proposed that PRKCZ and PGK1 could be novel therapeutic targets for prostate cancer. These investigations would not only aid in understanding the molecular mechanisms by which PPARγ regulates disease targets but would also lead to the identification of novel PPARγ gene targets.